2016
DOI: 10.1093/bja/aew185
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid volume in neonates undergoing spinal anaesthesia: a descriptive magnetic resonance imaging study

Abstract: The amount of spinal CSF in neonates can be estimated as 2 ml kg(-1) in both term and formerly preterm neonates. A difference in the CSF volume between them does not provide an explanation for a shorter duration of SA in the latter. Our findings reinforce weight-adjusted dosage of SA in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Additionally, spinal CSF volume was not as large as previously reported in neonates . Rochette et al also reported that the spinal CSF volume, from the first thoracic vertebra to the caudal end, was 1.97 (0.54) mL/kg in preterm and term neonates, which was similar to the present study. The spinal CSF volume reported by Rochette et al and the present study are half of the previously reported CSF volumes…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Additionally, spinal CSF volume was not as large as previously reported in neonates . Rochette et al also reported that the spinal CSF volume, from the first thoracic vertebra to the caudal end, was 1.97 (0.54) mL/kg in preterm and term neonates, which was similar to the present study. The spinal CSF volume reported by Rochette et al and the present study are half of the previously reported CSF volumes…”
Section: Discussionsupporting
confidence: 90%
“…This study has extended previous work on CSF analyses in neonates and children younger than 3 years of age to also include older children. Therefore, it is the first study that describes the developmental change in CSF volumes and their relationships with age, height, and weight across broad pediatric age groups, from neonates and infants to adolescents.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations